Effect of neuromuscular electrical stimulation associated with swallowing-related muscle training for post-stroke dysphagia: A protocol for systematic review and meta-analysis. Issue 11 (19th March 2021) - Du, Bosong; Li, Yan; Zhang, Bingran; Zhao, Wenjun; Zhou, Li
Abstract: Background: Swallowing dysfunction is a common dysfunction after stroke, and its incidence exceeds 50%. Aspiration pneumonia and malnutrition induced by dysphagia not only cause psychological shock to patients after stroke, but also burden the medical payment. Neuromuscular electrical stimulation, which stimulates the cortex and cortical bulb pathways to improve swallowing function, has been one of the emerging treatments for the post-stroke deglutition disorder. These therapy operators require the proficiency in professional knowledge, limiting clinical large sample studies, so there is an absence of evidence-based medicine. The research is to evaluate the effectiveness of neuromuscular electrical stimulations combined with swallowing-related muscle training to treat swallowing dysfunction after stroke. Methods: Computer retrieval performed in the 9 databases, including PubMed, Embase, Web of science, Cochrane Library, ClinicalTrials, China Biomedical Literature Database (CBM), China Knowledge Network Database (CNKI), Wanfang Database (WanFang), and China VIP Database (VIP). Taking the published literature from the establishment of the database until December 20, 2020. Literature searching is related to neuromuscular electrical stimulation randomized controlled trials on the effect of swallowing in stroke. In addition, we will do the manual search in Baidu Academic and Google Academic database as a supplementary search. The correlative randomized controlled clinical studies retrieval time range from the establishment of the database to December 20, 2020. Two investigators will screen the literature according to the inclusion and exclusion criteria independently, during that period they will evaluate the quality of the included studies and extract data from studies. The extracted data are dichotomous data will be represented by relative risk, continuous data will be represented by mean difference or standard mean deviation. If there exists heterogeneity and the final data summary analysis select random effect model. On the contrary, the fixed effect model is selected. Then, RevMan5.3 software was used when analyzing included literature. Meanwhile, the analysis results were illustrated by drawing. Results: This review will summarize available trials aimed at providing a comprehensive estimation of effectiveness of neuromuscular electrical stimulation associated with swallowing muscle training for post-stroke dysphagia. Conclusion: This review based on a comprehensive analysis of currently published randomized controlled trials on post-stroke dysphagia, that provide reliable evidence-based medicine evidence for the efficacy of neuromuscular electrical stimulation associated with swallowing rehabilitation training. Registration number: INPLASY202110009.